THE EFFECT OF TEACHER PROFESSIONAL COMPETENCE AND LEARNING FACILITY ON STUDENTS’ LEARNING MOTIVATION (Indonesian Journal of Learning and Instruction, 2018)
This research aims to find out the effect of teacher professional competence and learning facility on students learning motivation. The research method used by the researcher is the survey method. For the measurement uses Likert scale 5 options spreaded to 174 respondents. From the result of validity test, the variable X1 had 18 valid items, the variable X2 had 20 valid items, and variable Y had 18 valid items. The instrument reliability for the three variables are reliable. The data analysis uses double regression. Based on the result of the research, the questionnaire score gained for variable X1, variable X2 and variable Y was categorized high criterion. Based on the result of calculation of double regression analysis, it shows that teacher professional competence and learning facility had positive and significant effect on students learning motivation both partially and simultaneously. Therefore, to increase the students learning motivation, the teacher professional competence and learning facility should be increased, those are: 1) Teacher should master the learning material and improve the attractive learning method or media to increase students learning motivation; 2) The teacher should create pleasant learning atmosphere so the learning process can run effectively; 3) The students are expected to increase their reading so they can utilize their own ability and not depend on other’s opinion. Keywords: teacher competence; learning facility; learning motivation.